An Analysis of Spatial Patterns of Disabled Persons in West Bengal - Islam, MD Monirul (The Center for Disability Studies and Services Brawijaya University, 2017)
In this paper an attempt has been made to observe the spatial patterns of disabled persons by sex and residence in and across the districts of West Bengal. The research paper is exclusively based on secondary sources of data which have been taken from Census of India publications, New Delhi. Advanced statistical techniques have been used to analyze the data. Apart from, advanced cartographic techniques and GIS-MapInfo has also been used to visual representation of the data. The study reveals that disabled persons are highly concentrated in southern part of the state while, central part and a little area of northern part have the lower concentration. There is an enormous regional variation in the distributional patterns of male-female and rural-urban areas of the state. The study also examined the probable association between disability and selected socio-economic variables and it is observed that several variables are significantly associated with disability.